2009
DOI: 10.1136/hrt.2009.167213
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vascular function: flow-mediated constriction complements the information of flow-mediated dilatation

Abstract: In the first protocol, FMD and L-FMC were shown to be reciprocally regulated. A blunted FMD may, in certain cases, be an expression of increased resting vascular activation and not only of impaired endothelial function. In the second protocol, a statistical approach showed that implementation of L-FMC provides a better characterisation than FMD of vascular function in cardiovascular disease. Vascular (endothelial) function is a complex phenomenon which requires a multifaceted approach; it is suggested that a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 20 publications
8
81
1
Order By: Relevance
“…Some authors have described radial artery vasoconstriction during low flow and suggested that this is an additional marker of endothelial function [11][12][13][14][15][16] . However, the low-flowmediated vasoconstriction (L-FMC) seems to be specific to the radial artery because it has not been consistently described for the brachial artery.…”
Section: Ultrasound Study Proceduresmentioning
confidence: 99%
“…Some authors have described radial artery vasoconstriction during low flow and suggested that this is an additional marker of endothelial function [11][12][13][14][15][16] . However, the low-flowmediated vasoconstriction (L-FMC) seems to be specific to the radial artery because it has not been consistently described for the brachial artery.…”
Section: Ultrasound Study Proceduresmentioning
confidence: 99%
“…The technique of measuring L-FMC also differs in cuff position; most authors place the pneumatic cuff distal to the side of arterial diameter measurement 29) , while others use the proximal cuff occlusion method 30) . Low-flow-mediated constriction is calculated as the percentage decrease in arterial diameter in the last 30s of cuff occlusion (after 4.5 min of 5 min occlusion) as compared with resting diameter 31) ; however, FMD is determined in the 5 min following cuff deflation.…”
Section: Peripheral Arterial Tonometrymentioning
confidence: 99%
“…All patients abstained from vasoactive medications on the day of the studies. All patients in the middle-aged adult, smoking, HTN, and HF groups, as well as 27 patients with CAD and 14 healthy volunteers, were included in previous studies testing end points not related to the present study or to time-domain end points of FMD (18,19).…”
Section: Flow-mediated Dilation (Fmd) Is a Noninvasive Techniquementioning
confidence: 99%